2016
DOI: 10.1007/s12571-016-0617-3
|View full text |Cite
|
Sign up to set email alerts
|

Linking farm diversification to household diet diversification: evidence from a sample of Kenyan ultra-poor farmers

Abstract: The designations employed and the presentation of material in this information product do not imply the expression of any opinion whatsoever on the part of the Food and Agriculture Organization of the United Nations (FAO) concerning the legal or development status of any country, territory, city or area or of its authorities, or concerning the delimitation of its frontiers or boundaries. The mention of specific companies or products of manufacturers, whether or not these have been patented, does not imply that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 29 publications
12
60
0
1
Order By: Relevance
“…The model output indicates that holding other variable constant, for a one unit increase in age of household head's odds ratio in favor of high category with household dietary diversity increases by the factor of 1.353. Some previous reports appear to be claiming the opposite (Jones et al, 2014;Romeo et al, 2016;Ochieng et al, 2017).…”
Section: Econometric Analysismentioning
confidence: 90%
“…The model output indicates that holding other variable constant, for a one unit increase in age of household head's odds ratio in favor of high category with household dietary diversity increases by the factor of 1.353. Some previous reports appear to be claiming the opposite (Jones et al, 2014;Romeo et al, 2016;Ochieng et al, 2017).…”
Section: Econometric Analysismentioning
confidence: 90%
“…For example, Sibhatu et al [53] found that improving small farmers' access to markets seems to be a more effective strategy in improving nutrition than promoting production diversity on subsistence farms. Similarly, Romeo et al [48] conclude that agricultural production diversification is positively and significantly associated with household dietary diversity, but livestock ownership shows stronger significant level in comparison with production diversification, thereby implying that supporting investments in diversified livelihood system in general and livestock in particular are required to increase household dietary diversity. Djokoto et al [12] concluded that vegetable diversification offers great potential for improving livelihood of cocoa-based farm households in Ghana.…”
mentioning
confidence: 99%
“…The existing literature is mainly focused on the relationship between farm and dietary diversification. Romeo et al (2016) find a positive association between farm production diversification and household dietary diversity in East Africa. This correlation was especially strong with poultry ownership, probably due to an income effect, and with cattle holdings, that increased milk consumption due to a production-for-own-consumption effect.…”
Section: Livestock Food Security and Women's Empowermentmentioning
confidence: 67%